Design of Embedded Control System with Fuzzy Controller and Nonlinear Controller for the Line Follower Robot - Chiem, Nguyen Xuan; Nguyen, Nguyen Cong Binh (Peneliti Teknologi Teknik Indonesia, 2025)
In this paper, an embedded system for motion control of a Line Follower Robot (LFR) is presented. Line Follower Robot can change direction by changing the relative rotational speed of the wheels, and thus does not require additional steering motion. A robot designed at the Control Systems Laboratory, Le Quy Don Technical University, is chosen as the research platform in this paper. A fuzzy logic controller has been used to ensure the smallest position and angle deviation. The rules of the fuzzy logic controller are built based on the successor's experience when considering the Lyapunov function. The output of this controller is linear velocity and angular velocity, which are the achieved values ​​for the robot dynamics control loop. A nonlinear controller with blocked signals is synthesized based on the synergetic control theory (STC). The combination of control laws ensures the system is stable enough to measure noise and uncertainties in the robot's model and parameters. In addition, we realize that the control system is embedded. Simulation and experimental results with different scenarios demonstrate the effectiveness of the proposed control law.